Hypervirulent Acinetobacter baumannii (hvAB): The Convergence of Virulence and Multidrug Resistance - Nan Wu; Xinqian Ma; Wentao Ni (Antibiotics)
Acinetobacter baumannii has become a formidable pathogen in healthcare systems worldwide, primarily due to its remarkable capacity to develop multidrug resistance and cause life-threatening infections. While traditionally A. baumannii is considered an opportunistic pathogen of low virulence, accumulating evidence now underscores the emergence of hypervirulent A. baumannii (hvAB) strains. These strains combine heightened pathogenicity with extensive drug resistance, posing unprecedented challenges for clinical management and infection containment. This review comprehensively explores the molecular mechanisms driving hvAB’s virulence and antimicrobial resistance and its evolutionary trajectory, clinical presentations, and global epidemiology. Additionally, we evaluate potential therapeutic strategies and their broader public health implications.